Organizational Effectiveness Enhancememt Through the Lens of Lifelong Learning - Vithayaporn, Sanhakot (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Due to the 21st century’s global economic competitiveness, organizations increasingly recognize the need for ongoing learning and development, particularly non-formal education, and informal learning in the workplace, to achieve business results. This study aims to examine the impact of lifelong learning on organizational effectiveness and its importance. In the methods and resources, a systematic literature review with inclusion and exclusion criteria and a documentation analysis technique were used. Additionally, the meta-analysis technique was used to identify, select, conceptualize, and analyze data. The findings affirm that non-formal education providers are necessary for ongoing training and development, while informal learning is a cost-effective approach to increase education. This paper presents the concepts of lifelong learning in the European and Thai contexts as a major organizational effectiveness element. The current situation of Covid-19 through the perspective of lifelong learning is also presented to support the transformative learning theory. The discussion and conclusions describe that lifelong learning is a critically important factor that has a major impact on organizational effectiveness; meanwhile, leaders and Human Resources Development play vital strategic roles as learning system providers to enhance organizational effectiveness.